Maintaining financial success and expanding into other markets at feedmypet.com - Drake, Matt (Matthew J.); Wood, Charles A. (Pearson, 2014)
This new business analytics case study challenges readers to help a successful e-commerce startup use IPO funding to extend its niche leadership into new ventures, dissuade online competitors, and move long-time "bricks and mortar" shoppers online. Crystallizing realistic analytical challenges faced by companies in many industries and markets, it exposes readers to the entire decision-making process, providing opportunities to perform analyses, interpret output, and recommend the best course of action. Author: Charles A. Wood, Duquesne University